A failure of meiotic chromosome segregation in a fbh1Delta mutant correlates with persistent Rad51-DNA associations. - Sun, W; Lorenz, A; Osman, F; Whitby, M (Oxford University Press, 2011)
The F-box DNA helicase Fbh1 constrains homologous recombination in vegetative cells, most likely through an ability to displace the Rad51 recombinase from DNA. Here, we provide the first evidence that Fbh1 also serves a vital meiotic role in fission yeast to promote normal chromosome segregation. In the absence of Fbh1, chromosomes remain entangled or segregate unevenly during meiosis, and genetic and cytological data suggest that this results in part from a failure to efficiently dismantle Rad51 nucleofilaments that form during meiotic double-strand break repair.